Mono-/polyintoxication with 5F-ADB: A case series. (August 2019) - Kraemer, Michael; Fels, Helena; Dame, Torsten; Musshoff, Frank; Halter, Sebastian; Mogler, Lukas; Hess, Cornelius; Madea, Burkhard; Maas, Alexandra
Highlights: Presentation of five intoxication cases involving 5F-ADB. Analytical confirmation of 5F-ADB and its metabolites. Description and discussion of effects probably caused by 5F-ADB. Abstract: 5F-ADB is an indazole-based synthetic cannabinoid. In recent years, it has been detected in legal high products as well as in biological samples and is associated with serious adverse health, behavioral effects and even death. Due to the fast pace of the market of synthetic cannabinoids, data on such newly appearing substances are scarce. As pharmacological properties are often investigated in vitro or by using animal experiments, reports on synthetic cannabinoid findings in human samples along with corresponding case history descriptions are valuable for the interpretation of upcoming routine cases. Herein we report five cases with verified 5F-ADB consumption, including three fatalities, a case of driving under the influence of drugs as well as a case of grievous bodily harm. In four cases, 5F-ADB could be detected in blood or plasma. Concentrations were in the range of 0.11–0.57 μg/L. In one instance 5F-ADB consumption was verified by the detection of 5F-ADB metabolites in postmortem body fluids. The described cases illustrate various adverse effects including confusion (possibly even psychosis), collapse, loss of consciousness, unsafe driving style or changing moods that might be attributed to 5F-ADB.